2016
DOI: 10.1002/aur.1710
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the acoustic startle response and its modulation in children with typical development and those with autism spectrum disorders: A one‐year follow‐up

Abstract: Auditory hyper-reactivity is a common sensory-perceptual abnormality that interrupts behavioral adaptations in autism spectrum disorders (ASD). Recently, prolonged acoustic startle response (ASR) latency and hyper-reactivity to weak acoustic stimuli were reported in children with ASD. Indexes of ASR and its modulation are known to be stable biological markers for translational research in the adult population. However, little is known about the stability of these indexes in children. Thus, the objective of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Development of auditory circuitry depends on SERT, and altered 5‐HT receptors are found in the auditory cortex of ASD patients (Egaas et al, 1995; Lebrand et al, 1996, 1998). These data corroborate reports of sensory hypersensitivity in ASD (Baron‐Cohen et al, 2009; Gomes et al, 2008; Hitoglou et al, 2010; Kohl et al, 2014; Leekam et al, 2007; Takahashi et al, 2016; Tavassoli et al, 2014). Another study using fMRI showed that ASD patients had aberrant connectivity between sensorimotor and prefrontal regions as well as increased connectivity between the amygdala and the pulvinar nucleus, suggesting reduced thalamo‐cortical inhibition and increased thalamo‐amygdalar connections (Green et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Development of auditory circuitry depends on SERT, and altered 5‐HT receptors are found in the auditory cortex of ASD patients (Egaas et al, 1995; Lebrand et al, 1996, 1998). These data corroborate reports of sensory hypersensitivity in ASD (Baron‐Cohen et al, 2009; Gomes et al, 2008; Hitoglou et al, 2010; Kohl et al, 2014; Leekam et al, 2007; Takahashi et al, 2016; Tavassoli et al, 2014). Another study using fMRI showed that ASD patients had aberrant connectivity between sensorimotor and prefrontal regions as well as increased connectivity between the amygdala and the pulvinar nucleus, suggesting reduced thalamo‐cortical inhibition and increased thalamo‐amygdalar connections (Green et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Auditory hypersensitivity is observed in children with ASD (Baron‐Cohen et al, 2009; Gomes et al, 2008; Hitoglou et al, 2010; Kern et al, 2006; Kohl et al, 2014; Leekam et al, 2007; Takahashi et al, 2016). Previous studies found altered sensorimotor responses in rodents developmentally exposed to SSRIs; e.g., paroxetine exposure (s.c.) from P0‐8 disrupts thalamocortical somatosensory barrel fields in rats (Xu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…No consistent deficit has been noted in individuals with ASD. Children and adults with ASD without cognitive deficits had normal or even higher PPI except as reported in a study that used a specific parametric condition . Children and adults with autism with cognitive deficits had normal PPI .…”
Section: Rdoc Domain Constructs In Mouse Models Of Cnvmentioning
confidence: 80%
“…A commercial computerized human startle-response monitoring system (Startle Eyeblink Reflex Analysis System Map1155SYS, Nihonsanteku Co., Osaka, Japan) was used to deliver acoustic startle stimuli and to record and score the corresponding electromyographic activity. The specific methods for stimulus presentation and eyeblink acquisition have been described in detail previously (Takahashi et al, 2017, 2018). The following startle measures were examined: (1) ASR65, ASR75, ASR85, ASR95, and ASR105: average ASR eyeblink magnitude in response to pulse intensities of 65, 75, 85, 95, and 105 dB SPL, respectively; (2) the peak-ASR latency, defined as the average peak-ASR latency across trials with an ASR larger than 60 μV; (3) habituation of the ASR during the session, defined as the percentage of ASR amplitude reduction at 105 dB SPL and (4) PPI65, PPI70, PPI75: PPI at prepulse intensities of 65, 70, and 75 dB SPL, respectively.…”
Section: Methodsmentioning
confidence: 99%